Reinheit als Differenz Identität und Alterität in Max Frischs frühem Erzählwerk - Schmid, Lukas (Chronos Verlag, 2016)
Purity as Difference Identity and Alterity in Max Frisch`s early fiction This study investigates the early fiction of Max Frisch, previously only margin-ally discussed, in particular his first novel, «Jürg Reinhart. Eine sommerliche Schicksalsfahrt» (1934), the novella «Antwort aus der Stille» (1937), as well as the sequel to the Reinhart story, «J'adore ce qui me brûle oder Die Schwierigen». It uses previously unknown sources to reconstruct the creative origins of these works. Deploying a discourse analysis, this book employs analytical techniques from gender and postcolonial studies to deconstruct is-sues of ethnicity, nationalism, gender, and class. The three texts, and their constructions of identity and alterity are contextualized within the contested zone of ‹purity› and ‹difference› and relevant fields of discourse. «Antwort aus der Stille» is investigated within the Alpine discourse, including its nationalistic, gender-political and sexist extensions, «Jürg Reinhart» in the anti-Semitic, Orientalist, Balkan and Slavic discourses, and «J'adore ce qui me brûle» in the contemporary discourse of emancipation and gender issues, and especially in the discourse of eugenics and its Social Darwinist implications.